1976
DOI: 10.1177/000331977602701201
|View full text |Cite
|
Sign up to set email alerts
|

Venous Pressure and Compliance of the Peripheral Capacitance Vessels

Abstract: Compliances of the peripheral capacitance vessels decreased gradually in accordance with the increase in pressure of the brachial vein. The relationship between them formed a number of hyperbolic-like curves, the same results as those found in many cases of both normal subjects and patients with congestive heart failure. The decrease of compliance of the peripheral capacitance vessels was not the result of an organic change, but of a functional change of the vessels caused by distention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Therefore, care should be taken when extrapolating these results to other populations. Interestingly, alterations in limb venous compliance have been documented in numerous conditions in humans including healthy aging (6,10,20,23,31,34), endurance training (10,20), orthostatic intolerance (3,4,29), diabetes (1,27), heart failure (14,15), multiple system atrophy (17), spinal cord injury (5,12,32,33), and between sexes (10,16,18,19,21). The findings obtained by using VOP to assess venous parameters in such physiological states are limited in that they provide a global index of overall limb venous function, and whether these changes are reflective of alterations at the level of a single vein is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, care should be taken when extrapolating these results to other populations. Interestingly, alterations in limb venous compliance have been documented in numerous conditions in humans including healthy aging (6,10,20,23,31,34), endurance training (10,20), orthostatic intolerance (3,4,29), diabetes (1,27), heart failure (14,15), multiple system atrophy (17), spinal cord injury (5,12,32,33), and between sexes (10,16,18,19,21). The findings obtained by using VOP to assess venous parameters in such physiological states are limited in that they provide a global index of overall limb venous function, and whether these changes are reflective of alterations at the level of a single vein is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Sharp objects typically produce linear incisions with clearly defined edges, while blunt impacts can result in more complex wounds that are particularly challenging to seal. [ 48 ] To investigate the feasibility of using F20HD5 hydrogel to seal complex corneal lacerations, an ex vivo study was further conducted using two additional types of full‐thickness corneal lacerations: corneal T‐shaped incisions and corneoscleral linear incisions ( Figure ). The incisions were created using a surgical 15° stab knife on freshly enucleated porcine eyes.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance of the vein is reported to be approximately 100 dyne/sec/cm, 5 about one-fifteenth to one-twentieth of the artery, while its capacity is about 25 (18 to 30) times that of the artery. 15 It has been reported that the innervation of sympathetic vasoactive fibers on veins grows stronger as one moves away from a central site to a peripheral area. 16 When these characteristics of the venous system are applied to blood circulation in a venous flap, the following speculations can be raised.…”
Section: Mechanism Of Venous Flapmentioning
confidence: 99%